Stiffness enhancement of magnetorheological foam by structural modification using silica nanoparticles additive - Khaidir, Rahayu Emilia Mohamed; Nordin, Nur Azmah; Mazlan, Saiful Amri; Abd Rahman, Hamimah; Ubaidillah,; Abdul Aziz, Siti Aishah; Nazmi, Nurhazimah (Frontiers in Materials, 2022)
Magnetorheological (MR) foam is a newly developed porous smart material that is able to change its properties continuously, actively, and reversibly in response to controllable external magnetic stimuli. Unfortunately, the stiffness or also known as storage modulus of MR foam is still rather low and insufficient, in the range of below 100 kPa only, due to weak interparticle interaction between CIPs and the foam matrix, which consequently restricts the potential of MR foam to be used in future sensor applications or in other semi-active devices. Therefore, the aim of this research is to enhance the structural and storage modulus of MR foam by adding silica nanoparticles as an additive. Consequently, MR foam samples with different compositions of silica nanoparticles in the range of 0–5 wt% were prepared via an in situ method. The rheological properties were tested under an oscillatory shear mode with the absence and presence of magnetic fields using a rheometer, with the input parameters of strains between 0.001% and 10% and range of magnetic flux density between 0 and 0.73 T for a magnetic field sweep test. The rheological findings show that with the addition of silica nanoparticles, particularly at 4 wt%, have enhanced the storage modulus of MR foam by 260%, which attributed to the highest stiffness from 45 to 162 kPa. Meanwhile, the change of storage modulus under the influence of magnetic fields (0 T–0.73 T) somehow showed small increment, about ∆1 kPa for each concentration of silica nanoparticles in MR foams, due to non-magnetic behavior of silica. The morphological characteristics of MR foams were described by an elemental analysis carried out by a using variable pressure scanning electron microscope (VPSEM) equipped with energy dispersive x-ray spectroscopy (EDX). The micrographs demonstrated large open-cell pores for MR foam, while MR foam with silica nanoparticles exhibited more closed-cell pores, associated with the enhancement of its storage modulus. It indicates that the silica nanoparticles have encouraged well dispersion of the particles in the foam matrix, which improved and strengthened the microstructure of MR foams through formation of silane coupling bonds of silica in the filler-matrix structure. Overall, incorporation of silica nanoparticles as an additive in the MR foam could provide advantage in enhancing the structure and mechanical properties of MR foam, for various future smart devices.